2005
DOI: 10.1177/1534582305285861
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing in the Posterior Parietal Cortex

Abstract: Goal-directed behavior can be characterized as a dynamic link between a sensory stimulus and a motor act. Neural correlates of many of the intermediate events of goal-directed behavior are found in the posterior parietal cortex. Although the parietal cortex's role in guiding visual behaviors has received considerable attention, relatively little is known about its role in mediating auditory behaviors. Here, the authors review recent studies that have focused on how neurons in the lateral intraparietal area (ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 214 publications
1
40
0
1
Order By: Relevance
“…For instance, in the monkey, the parietal area VIP receives inputs from visual, auditory, somatosensory, vestibular, motor and polysensory areas (Duhamel et al, 1998) that confer typical multimodal responses to the VIP neurons (Bremmer et al, 2002;Schlack et al, 2005;Avillac et al, 2007). Similarly, the connectivity pattern of the LIP Blatt et al, 1990;Lewis and Van Essen, 2000) is consistent with the multisensory properties reported for LIP neurons (Cohen et al, 2005;Russ et al, 2006;Gottlieb, 2007). The ventral part of LIP connects with areas dealing with spatial information (visual area MT and the auditory caudiomedial area; Andersen et al, 1997), as well as with the frontal eye field (Schall et al, 1995), whereas the dorsal part of LIP is connected with areas responsible for the processing of visual information related to the form of objects in the inferotemporal cortex (ventral ''what" visual pathway).…”
Section: Heteromodal Connections: Connections Between Different Sensosupporting
confidence: 66%
“…For instance, in the monkey, the parietal area VIP receives inputs from visual, auditory, somatosensory, vestibular, motor and polysensory areas (Duhamel et al, 1998) that confer typical multimodal responses to the VIP neurons (Bremmer et al, 2002;Schlack et al, 2005;Avillac et al, 2007). Similarly, the connectivity pattern of the LIP Blatt et al, 1990;Lewis and Van Essen, 2000) is consistent with the multisensory properties reported for LIP neurons (Cohen et al, 2005;Russ et al, 2006;Gottlieb, 2007). The ventral part of LIP connects with areas dealing with spatial information (visual area MT and the auditory caudiomedial area; Andersen et al, 1997), as well as with the frontal eye field (Schall et al, 1995), whereas the dorsal part of LIP is connected with areas responsible for the processing of visual information related to the form of objects in the inferotemporal cortex (ventral ''what" visual pathway).…”
Section: Heteromodal Connections: Connections Between Different Sensosupporting
confidence: 66%
“…Other association cortical areas in the attentional network (Posner and Peterson, 1990) are also activated in auditory attention -such the posterior parietal cortex (Cohen et al, 2005;Yantis, 2004, 2006), and right inferior frontal and dorsolateral prefrontal cortex (Voisin et al, 2006). Moreover, neuroimaging studies of the thalamus (Frith and Friston, 1997) and physiological (McAlonan et al, 2006) and neuroanatomical (Sakoda et al, 2004) studies of the thalamic reticular nucleus suggest that the different thalamic nuclei may play important roles in attentional modulation and in helping direct the shifting focus of attention (Crick, 1984).…”
Section: I3 Neural Locus Of Auditory Attentionmentioning
confidence: 99%
“…Attention may also be instrumental in shifting from one cortical state to another. A recent study by Blake and colleagues (2006) demonstrates that a combination of acoustic stimuli and reward are insufficient to evoke cortical plasticity in the absence of an active, behavioral link between the two, and emphasizes the importance of forging dynamic links between sensory stimuli and motor actions during task learning (Cohen et al, 2005).…”
Section: I5 Exploring the Link Between Attention And Receptive-fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to probe the underlying neural mechanisms of the ventriloquist effect at the single neuron level, a suitable animal model where invasive studies can be conducted needs to be identified. Studies have documented several critical regions of the nonhuman primate brain that have multisensory responses, including the superior temporal sulcus (e.g., Benevento, Fallon, Davis & Rezak, 1977;Bruce, Desimone & Gross, 1981, Cusick, 1997, the parietal lobe (e.g., Cohen, Russ & Gifford, 2005, Mazzoni, Bracewell, Barash & Andersen, 1996, Stricanne, Andersen & Mazzoni, 1996, and the frontal lobe (Benevento et al, 1977;Russo & Bruce, 1994). Each of these areas could potentially be involved in multisensory processing that leads to the spatial ventriloquism effect.…”
Section: Single Neuron Approachmentioning
confidence: 99%